Quantum Bio-inspired Vision Model on System-on-a-Chip (SoC) - Chu Kiong, Loo; Teh Joo, Peng (2008)
This paper presents the quantum-like 'brain' for humanoid and experimentally proves a 2D invariant object recognition model inspired by the image processing along the human visual pathway: retina, lateral geniculate nucleus (LGN) and primary visual cortex (VI). It also describes storing the output of the model in quantum holographic memory (a hologram) and the method to reconstruct the Visual representation. The work is implemented as system-on-a-chip in field-programmable gate array (FPGA).